Transparency and Liquidity: A Controlled Experiment on Corporate Bonds - Goldstein, Michael A.; Hotchkiss, Edith S.; Sirri, Erik R. (Review of Financial Studies, 2007)
This article reports the results of an experiment designed to assess the impact of last-sale trade reporting on the liquidity of BBB corporate bonds. Overall, adding transparency has either a neutral or a positive effect on liquidity. Increased transparency is not associated with greater trading volume. Except for very large trades, spreads on newly transparent bonds decline relative to bonds that experience no transparency change. However, we find no effect on spreads for very infrequently traded bonds. The observed decrease in transaction costs is consistent with investors’ ability to negotiate better terms of trade once they have access to broader bond-pricing data. (JEL codes: G14, G18, G23, G24, G28)